UJI ANTIMIKROBA FRAKSI III DAUN KRATOM (Mitragyna speciosa) TERHADAP BAKTERI Staphylococcus aureus - Tri Puji Lestari Sudarwati (Akademi Farmasi Yarsi Pontianak, 2021)
Kratom (Mitragyna speciosa Korth) is a type of plant found in forest areas in Indonesia which contains chemical compounds such as alkaloids, flavonoids, phenols, terpenoids, steroids, triterpenoids, tannins, and saponins. In this study, the antimicrobial potency of fraction III of kratom leaves was tested by column chromatography separation. Kratom leaves have several benefits, one of which is as an antimicrobial. The extraction process chosen is the maceration method. The results obtained from column chromatography were then grouped based on RF values ​​using the thin layer chromatography method, from 80 vials the RF value calculated in the TLC test of kratom leaf methanol extract obtained a value of 0.84. Then the results obtained were made with concentrations of 2%, 4%, 6%, 8% and 10% for the antibacterial activity test. The antibacterial activity test was repeated 5 times and the results of the inhibition zone with an average concentration of 2% obtained data of 2,436 mm, a concentration of 4% obtained an average of 1,616 mm, a concentration of 6% obtained an average of 0.685 mm, a concentration of 8% obtained an average of 0.685 mm. an average of 0.596 mm, while for a concentration of 10% the average was 0.96. From the results of this study, it can be concluded that kratom leaf extract (Mitragyna speciosa) using methanol with column chromatography separation method has antibacterial activity against Staphylococcus aureus with a weak category.